2022
DOI: 10.3389/fdata.2021.769726
|View full text |Cite
|
Sign up to set email alerts
|

Coming Together of Bayesian Inference and Skew Spherical Data

Abstract: This paper presents Bayesian directional data modeling via the skew-rotationally-symmetric Fisher-von Mises-Langevin (FvML) distribution. The prior distributions for the parameters are a pivotal building block in Bayesian analysis, therefore, the impact of the proposed priors will be quantified using the Wasserstein Impact Measure (WIM) to guide the practitioner in the implementation process. For the computation of the posterior, modifications of Gibbs and slice samplings are applied for generating samples. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It helps us to choose between two or more given priors. Nakhaei Rad et al 44 by using the WIM measure demonstrated that the combination of the von Mises, gamma and truncated normal distributions decreases the execution time in the Gibbs sampling algorithm. Thus, providing accurate parameter estimates for the skew Fisher-von Mises distribution 51 as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It helps us to choose between two or more given priors. Nakhaei Rad et al 44 by using the WIM measure demonstrated that the combination of the von Mises, gamma and truncated normal distributions decreases the execution time in the Gibbs sampling algorithm. Thus, providing accurate parameter estimates for the skew Fisher-von Mises distribution 51 as well.…”
Section: Methodsmentioning
confidence: 99%
“…From the preceding it follows there is a gap in the literature that inspired us to propose novel Bayesian analysis of skew directional wind data . Recently Nakhaei Rad et al 43 , 44 provided Bayesian analysis for skew von Mises-Fisher distribution and skew Wrapped Cauchy mixture model.…”
Section: Introductionmentioning
confidence: 99%